Implementasi Media Pembelajaran Sederhana Berbasis Digital Pada Mata Pelajaran Bahasa Arab - Muhammad Fadhly; Muhammad Alif Al Aziz; Bayu Sagara; Wismanto Wismanto (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
The application of learning media in Arabic language subjects has become an important focus in contemporary education. With technological developments, learning media can become an effective tool in improving students' understanding of Arabic, as well as enriching their learning experience. In this introduction, we will discuss the significance of using learning media in the context of teaching Arabic, as well as the potential benefits that students can obtain through this approach. This research aims to explore effective learning media selection strategies in the context of Arabic language learning. The research method used is a qualitative approach through case studies in a secondary education institution These findings contribute to the development of more effective and innovative Arabic language learning strategies. This research also highlights the importance of understanding the cultural context and students' needs in choosing appropriate learning media, and emphasizes the need for training and developing teacher professionalism in implementing learning media effectively in Arabic language learning.